HOME CARE FOR CHILDREN USING A TRACHEOSTOMY: CAREGIVERS’ PERSPECTIVE IN THE AMAZON CONTEXT - Pereira, Iunaira Cavalcante; Flores, Paula Vanessa Peclat; Silva, Liliane Faria da (Cogitare Enfermagem, 2024)
Objective: To describe caregivers’ perception of tracheostomized children about the challenges in discharge to their homes in the Amazonian context. Method: A descriptive, qualitative study was conducted with 16 caregivers of tracheostomized children who experienced dehospitalization in a children’s hospital in Rio Branco – Acre – Brazil. Saturation-defined sampling, data collected with a semi-structured script from August to December 2021, submitted to Bardin Content Analysis. Results: the analysis resulted in four categories: (1) feelings experienced with the use of the tracheal device; (2) routine tracheostomy care that caregivers consider important; (3) questions and reports about tracheal aspiration; and (4) conduct in the face of complications in children using tracheostomy. Final remarks: the fear of learning the tracheal aspiration technique and of being discharged from the hospital reinforces the need for early and continuous education for caregivers, focusing on routine and emergency care for tracheostomized children.